Economic and political variables affecting the retiree’s personality: Research in social anthropology - Hateem, Ali Hussein (Al-Adab Journal, 2022)
From the statistics of the National Pension Agency until the end of 2018, the number of retirees in Iraq reached more than four million. These large numbers in themselves constitute a challenge to the state and society, especially with the weak services provided to this category. The study relied on the functional approach, the historical approach, and the comparative approach, and used data collection tools, including in-depth interviews, participatory observation, and electronic photography.